Comparison of malassezia colonization of 'Maskne' patients with seborrheic dermatitis cases and healthy individuals - Ayse N Atsu; Nazlı Caf; Zafer Türkoğlu; Defne Özkoca; Ozan Yıldırım; Çağrı Ergin (Wolters Kluwer Medknow Publications, 2022)
Background: With the Covid-19 pandemic, the use of masks has increased the frequency of 'maskne' cases. Local physiological changes due to the use of mask have caused changes in the presence of yeasts in the environment, such as acne and seborrheic dermatitis. Objectives: The aim is to compare the differences of Malassezia species in the maskne region. Materials and Method: A total of 408 subjects wearing masks at least 4 h a day for 6 weeks or longer, compromised of 212 acne patients, 72 seborrheic dermatitis sufferers, and 124 healthy volunteers were included in this study. Swab samples were taken for Malassezia cultures from nasolabial area and their control retro auricular region. The Statistical Package for Social Sciences (SPSS) version 22 was used for the statistical analysis. Results: Malassezia species was most frequently found in the nasolabial region of the seborrheic dermatitis group. Malassezia species were more commonly isolated from the nasolabial region of acne and seborrheic dermatitis patients, compared to the retroauricular region of each patient, than the healthy subjects. The rate of M. globosa isolated from the nasolabial region was high in all groups, the isolation rate of M. restricta was low (P < 0.05). Conclusion: As Malassezia species are more commonly isolated from the nasolabial region of acne and seborrheic dermatitis patients, the increasing numbers of Malassezia species will trigger inflammation with an antibody reaction against these yeasts. Treatment of resistant acne and seborrheic dermatitis will be facilitated with the knowledge of this inflammation.